2020
DOI: 10.1029/2020gl088206
|View full text |Cite
|
Sign up to set email alerts
|

What Caused the Large‐Scale Heat Deficit in the Subtropical South Atlantic Ocean During 2009–2012?

Abstract: The subtropical South Atlantic hosts complex ocean circulation patterns and processes that transport heat to the North Atlantic, thereby playing an important role in global energy redistribution. This study uses several oceanic products to assess ocean heat changes in the subtropical South Atlantic and the associated atmosphere‐ocean processes. A particular focus is placed on the large heat deficit during 2009–2012, which is associated with cooling during 2008–2011 and subsequent warming. This heat deficit was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The correlations at other three latitudes are quite low (Figure 13). This southward decrease in correlation is probably due in part to the accumulation of errors in the energy budget as it moves farther away from the North Pole, since the MHT at each latitude was estimated by integrating the net surface heat flux and changes in ocean heat content from that latitude to the North Pole, particularly considering the large uncertainties in the ocean heat content changes in the South Atlantic Ocean (Dong et al, 2020). Interestingly, the heat transport convergence (MHT 34.5S -MHT 20S ) from the two estimates agree well with correlation r = 0.71 (Figure 14), suggesting that our estimates capture the changes in heat content and air-sea heat fluxes in this region.…”
Section: 1029/2020jc017073mentioning
confidence: 99%
“…The correlations at other three latitudes are quite low (Figure 13). This southward decrease in correlation is probably due in part to the accumulation of errors in the energy budget as it moves farther away from the North Pole, since the MHT at each latitude was estimated by integrating the net surface heat flux and changes in ocean heat content from that latitude to the North Pole, particularly considering the large uncertainties in the ocean heat content changes in the South Atlantic Ocean (Dong et al, 2020). Interestingly, the heat transport convergence (MHT 34.5S -MHT 20S ) from the two estimates agree well with correlation r = 0.71 (Figure 14), suggesting that our estimates capture the changes in heat content and air-sea heat fluxes in this region.…”
Section: 1029/2020jc017073mentioning
confidence: 99%
“…The global mean sea surface temperature (SST) has increased by approximately 0.6 C from 1980 to 2020 and by 0.88 C from 2011 to 2020, related to 1850-1900 pre-industrial times (Fox-Kemper et al, 2021). Over the past 50 years, the ocean has absorbed more than 90% of the additional heat gained by the Earth's system (Dong et al, 2020). The areas where SST has changed most rapidly during these years, with a tendency to persist in the coming years, are called "hotspots" and are considered prime locations for assessing climate change impacts (Diffenbaugh et al, 2008;Frusher et al, 2013;Giorgi, 2006;Hobday & Pecl, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on those key regions are based on coarse resolution climate models (e.g., Haarsma et al, 2005; Wainer & Venegas, 2002), which do not explicitly represent mesoscale eddies in the ocean, or based on ocean‐only models (e.g., Durgadoo et al, 2013; Schwarzkopf et al, 2019). Recent studies suggested that SST variability in the South Atlantic can also be remotely forced by changes in the tropical Pacific related to ENSO processes (e.g., Dong et al, 2020; Putrasahan et al, 2016) and Pacific multidecadal variability (Lopez, Dong, Lee, & Campos, 2016), which are due to natural interaction between the atmosphere and ocean. Therefore, high‐resolution coupled models may provide more insightful understanding of the mechanisms for changes in the South Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%